CHOROIDAL NEVUS TRANSFORMATION INTO MELANOMA PER MILLIMETER INCREMENT IN THICKNESS USING MULTIMODAL IMAGING IN 2355 CASES: The 2019 Wendell L. Hughes Lecture. Issue 10 (October 2019) - Shields, Carol L.; Dalvin, Lauren A.; Yu, Michael D.; Ancona-Lezama, David; Di Nicola, Maura; Williams, Basil K.; Lucio-Alvarez, J. Antonio; Ang, Su Mae; Maloney, Sean M.; Welch, R. Joel; Shields, Jerry A.
Abstract : Purpose: To analyze risk of nevus transformation into melanoma per millimeter increment. Methods: Retrospective analysis of 3, 806 choroidal nevi for transformation into melanoma per incremental millimeter thickness (flat [⩽1.0 mm], thin [1.1–2.0 mm], thicker [2.1–3.0 mm], and thickest [>3.0 mm]) Results: The median nevus thickness was 1.4 mm, and nevi were categorized (flat, thin, thicker, and thickest) in 1, 140 (30%), 2052 (54%), 555 (15%), and 59 (<1%), respectively. There were differences in tumor diameter (2.5, 4.8, 7.5, and 9.3 mm; P < 0.01), optical coherence tomography detection of overlying subretinal fluid (<1, 4, 15, and 11%; P < 0.01), overlying retinal edema (<1, 3, 14, and 25%; P < 0.01), overlying drusen (23, 49, 64, and 64%; P < 0.01), overlying retinal pigment epithelial detachment (1, 4, 4, and 9%; P < 0.01), and overlying lipofuscin hyperautofluoresence (<1, 3, 6, and 7%; P < 0.01). Choroidal nevus transformation into melanoma (n = 90/2, 355 cases, 3.8%) was found by Kaplan–Meier 7-year estimates (2.2, 6.1, 31.7, and 34.5%; P < 0.0001) and by hazard ratio (HR) compared with nevus ⩽1.0 mm (not available, 4.7 [ P = 0.01], 35.7 [ P < 0.0001], and 52.0 [ P < 0.0001]). For all thicknesses, those with growth displayed increase in mean basal diameter of 2.4 mm and thickness of 1.1 mm, optical coherence tomography increase in subretinal fluid (65%), autofluorescence increase in lipofuscin (40%), and ultrasonography increase in hollowness (30%). Multivariable risk factors, recalled by the mnemonic "To Find Small Ocular Melanoma Doing IMaging" (TFSOM-DIM) representing Thickness >2 mm (ultrasonography), Fluid subretinal (optical coherence tomography), Symptom vision loss (Va), Orange pigment (autofluorescence), Melanoma hollow (ultrasonography), and DIaMeter >5 mm, revealed factors per incremental thickness category (compared with flat) including thin (Fluid overlying, HR 6.1; DIaMeter >5 mm, HR 3.3), thicker (Fluid subretinal ⩽3 mm from nevus, HR 5.7; Melanoma acoustic hollowness, HR 2.7), and thickest (Orange pigment, HR 9.1). Conclusion: Each incremental increase in choroidal nevus thickness demonstrated risk of growth into melanoma with HR (compared with flat) 4.7 for thin, 35.7 for thicker, and 52.0 for thickest. The increase from ⩽2.0 mm to >2.0 mm thickness conferred the greatest rise for transformation. Abstract : Supplemental Digital Content is Available in the Text.Each millimeter increase in nevus thickness was associated with increasing risk of growth into melanoma with hazard ratio increasing from 4.7 for thin (1.1–2.0 mm), 35.7 for thicker (2.1–3.0 mm), and 52.0 for thickest (>3.0 mm) nevi, compared with flat (⩽1.0 mm) nevi. Increasing thickness of choroidal nevus poses increasing risk of transformation into melanoma.